Sejarah Pembelajaran Edutainment - Praja, Tatag Satria (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
The purpose of human life is happiness which is synonymous with pleasure. During this time, learning in class has been a scary thing. Many teachers force students to study a pile of learning material, giving rise to fear for students and even stress. Edutainment is learning to design by combining the content of education and entertainment in harmony, so that learning activities take place fun. Edutainment was formally introduced in the 1980s. Edutainment-based learning theory, among others: cooperative learning theory, triune brain, multiple intelligences, and Quantum learning. Learning concepts that support edutainment includes: The concept of a